Interaksi Sosial dalam Proses Pembelajaran - Lalu Moh. Fahri; Lalu A. Hery Qusyairi (LP2M STIT Palapa Nusantara, 2019)
This study aims to provide an overview of students' social interactions in the learning process for instructors and prospective teachers. In this article a number of things will be reviewed, including the meaning of social interaction and learning, forms of social interaction and learning, and interaction relationships with learning. After understanding the interaction in the learning process, instructors and prospective instructors are expected to understand that learning outcomes and learning processes must be balanced so that the educational process leads to the development of attitudes, intellectual intelligence, or the development of children's skills according to their needs.